RETRACTED: Short- and Long-Run Influence of Education on Subjective Well-Being: The Role of Information and Communication Technology in China - Wang, Zhenyu; Sohail, Muhammad Tayyab (Frontiers in Psychology, 2022)
Subjective well-being is defined as how happy and satisfied a person is in his life. To date, among the significant determinants of subjective well-being, national income is considered an important one. However, not much focus has been paid to other determinants of subjective well-being, such as education and ICTs. Therefore, this study aims to investigate the short and long-run impact of education and ICTs on subjective well-being in China over the period 1996 to 2020. To empirically investigate the nexus, we have employed bounds testing approach to cointegration and error correction modeling. The long-run estimates attached to education are positive and significant, implying that a rise in average years of schooling help increases the level of happiness. However, the long-run estimate attached to the internet is significant and positive in the happiness model. As far as the interaction term between education and the internet is concerned, the estimate is positive and significant. In short-run, the estimates of education, ICTs, and an interaction term between them are also significantly positive.